Transforming laboratory teaching assistants as teaching leaders. Issue 7 (10th November 2018) - Flaherty, A. A.; Overton, T. L.
ABSTRACT: Teaching assistants (TAs) are crucial components of laboratory teaching and learning processes and much research has been devoted to developing their teaching capabilities. However, much of this research has involved transmitting information about what good teaching is to TAs. This research study sought to employ an alternative way of catalysing laboratory TAs in their teaching roles. The Transforming Laboratory Leadership, Learning and Teaching programme (TLLLT) aimed to place emphasis on the development of TAs as leaders in line with the construct of transformational teaching. Here, a narrative inquiry approach was used to generate a space for TAs to reflect and discuss how their experiences, perceived capabilities, self-efficacy beliefs and attitudes towards teaching could implicate and inform their adoption of transformational teaching methods. Twenty-seven TAs with diverse levels of teaching experience participated in the TLLLT programme. Records of brainstorm discussions during the TLLLT programme provided the narrative to analyse how TAs envisioned their development as transformational teachers. Focus group interviews explored how TAs perceived their participation in the TLLLT programme to have influenced the learning environment in the laboratory. The findings of this research support TA teacher development to nurture TAs' development as leaders towards catalysing them in their teaching roles.